Experimental investigation on the effect of wear flat inclination on the cutting response of a blunt tool in rock cutting - Rostamsowlat, I.; Richard, T.; Evans, Brian (2018)
A vast majority of experimental researches focuses on the cutting action of a sharp cutter, while there has been limited experimental work devoted to the study of the contact process at the wear flat-rock interface. The specific objective of this study is to determine the effect of the wear flat inclination angle ( β ) with respect to the cutter velocity vector ( vv ) on both the contact stress ( σ ) and friction coefficient ( μ ) mobilized at the wear flat-rock interface. An extensive and comprehensive set of cutting experiments was carried out on thirteen different sedimentary quarry rock samples using a state-of-the-art rock cutting equipment. A unique cutter holder was purposely designed and manufactured along with a precise experimental protocol implemented in order to change the back rake angle and therefore the inclination β by steps of 0.10∘ . The experimental observations confirm the existence of three regimes of frictional contact (identified as elastic, elasto-plastic and plastic) for all rock samples. Further, the results suggest that the scaled contact stress is predominantly controlled by a dimensionless number η=E∗tanβq with E∗ the plane strain elastic modulus and q the rock strength.